Clinical effectiveness of fluorescence, digital images and ICDAS for detecting occlusal caries - Presoto, Cristina Dupim; Trevisan, Tamara Carolina; Andrade, Maria Costa De; Dantas, Andrea Abi-rached; Campos, Juliana Alvares Duarte Bonini; Oliveira-junior, Osmir Batista De (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
AbstractIntroduction The detection of small caries lesions is still a challenge for dental professionals who in their clinical practice have a wide variety of methods to detect caries on occlusal surfaces.Objective To clinically assess the effectiveness of the Vista Proof fluorescence camera, the Vista Cam digital intraoral micro camera and the International Caries Detection and Assessment System (ICDAS) visual criterion for detecting caries lesions on occlusal surfaces of permanent teeth.Material and method One hundred and seven posterior teeth from adult patients were examined visually and by means of digital radiographs by an examiner who rated them according to the presence or absence of occlusal caries. The teeth were then assessed by the other examiner using ICDAS, fluorescence and magnified digital images. The effectiveness of the methods was measured based on sensitivity, specificity, positive and negative likelihood ratio. For each method, the Receiver Operating Characteristic (ROC) curve and the Area Under the ROC curve (AUROC) were estimated.Result There was exceptional discrimination capacity for the intraoral images (AUROC=.93) and the ICDAS (AUROC=.91), with no significant statistical difference between them (z=.35, p=.73). The fluorescence exhibited an acceptable discrimination capacity (AUROC=0.78), although it was lower than the others. The positive likelihood ratio for the fluorescence was only 2.32, compared to 20.58 for the intraoral image and 58.11 for the ICDAS.Conclusion Both methods and the ICDAS exhibited an adequate clinical performance, although the ICDAS and intraoral image were more effective than the fluorescence.

ResumoIntrodução A detecção de pequenas lesões de cárie ainda é um desafio para profissionais da Odontologia, que em sua prática clínica dispõem de uma grande variedade de métodos para detectar cáries nas superfícies oclusais.Objetivo Avaliar clinicamente a efetividade da câmera de fluorescência Vista Proof, da microcâmera intraoral digital Vista Cam e do critério visual ICDAS (International Caries Detection and Assessment System) para detecção de lesões de cárie nas superfícies oclusais.Material e método Cento e sete dentes posteriores de pacientes adultos foram examinados visualmente e por meio de radiografias digitais por um examinador que os classificou de acordo com a presença ou ausência de cárie. Os dentes foram então avaliados por outro examinador que utilizou o ICDAS, fluorescência e imagens digitais ampliadas. A efetividade dos métodos foi mensurada por meio da sensibilidade, especificidade, razão de verossimilhança positiva e negativa. Para cada método, a curva ROC (Receiver Operating Characteristic) e a área sob a mesma - AUROC (Area Under the ROC curve) foram estimadas.Resultado Houve excepcional capacidade discriminante para as imagens intraorais (AUROC=0,93) e para o ICDAS (AUROC=0,91), com diferença estatística não significativa entre eles (z=0,35, p=0,73). A fluorescência apresentou capacidade discriminante aceitável (AUROC=0,78), embora tenha sido menor que os outros. A razão de verossimilhança positiva para a fluorescência foi 2,32, comparado a 20,58 para a imagem intraoral e 58,11 para o ICDAS.Conclusão Ambos os métodos e o ICDAS exibiram um adequado desempenho clínico, sendo que o ICDAS e a imagem intraoral foram mais efetivos que a fluorescência.
Efetividade clínica da fluorescência, imagens digitais e ICDAS na detecção de cárie oclusal
Keywords: Dental caries; effectiveness; diagnosis; fluorescence; Cárie dentária; efetividade; diagnóstico; fluorescência